In vivo assessment of secondary caries and dentin characteristics after traditional amalgam restorations - Pinheiro, Isauremi Vieira de Assunção; Borges, Boniek Castillo Dutra; de Lima, Kenio Costa (European Journal of Dentistry, 2012)
Objectives:This study aimed to evaluate in vivo the occurrence of secondary caries and dentin characteristics in permanent molars after traditional amalgam restorations, by means of clinical visual examination, radiographs and laser-induced fluorescence (LF) (DIAGNOdent).Methods:Thirty first permanent molars of 30 schoolchildren in the 7 to14 year-old age group were included. Caries was removed by hand. Thus, indirect pulp capping was performed with glassionomer cement (GIC), the cavity was varnished and amalgam filled. LF was measured before and after cavity preparation and after a 12-month observation period. Dentin color after cavity preparation and after the 12-month observation period was recorded. Recurrent caries was also investigated by visual clinical and radiographic examinations, in addition to dentin thickness between pulp and indirect GIC pulp capping. Data was analyzed by ANOVA for repeated measurements, paired “t” test and descriptive statistic.Results:There were statistically significant differences (P<.05) among LF scores for dentin in all periods evaluated, with the lowest scores shown after 12 month of observation. There was no statistical difference between dentin color after cavity preparation and following 12 months of observation. Moreover, there was no recurrent caries attack at 12-month follow-up; dentin thickness between pulp and indirect GIC pulp capping was similar between baseline and final observation periods. It was concluded that the clinical restorative procedure using hand caries removal, indirect pulp capping with GIC, varnishing and amalgam filling the cavity did not provide secondary caries and increased dentin mineral content after 12 months. (Eur J Dent 2012;6:263-269)
Keywords: Clinical trial; glass ionomer cement; emineralization; DIAGNOdent; recurrent caries